Potential Types of Herbal Plants in Bambapuang, District of Enrekang, South Sulawesi - Evi Anggraeni HR; Elis Tambaru; Muhtadin Asnady Salam; Andi Ilham Latunra (Universitas Hasanuddin, 2018)
Research on Plant Types of Potential Drugs in the village Bambapuang Enrekang was conducted in April-June 2017. This study aims to determine the types of plants that have the potential drug in the village Bambapuang Enrekang. The method used is the method of cruising cruise method. Results of research conducted at the Village Community Bambapuang shows that there are 53 species of plants used as medicine, consisting of two (2) Classis is Dicotyledoneae as much as 27 familia and Monocotyledoneae four (4) familia. Species most widely used of Classis Dicotyledoneae that soursop (40%), cat whiskers (36%) and guava (32%). Species involved are the least used of Classis Monocotyledoneae such as corn, ginger, bananas and dayak onions with a percentage of 4%. Organ of the plant most widely used as medicine are the leaves (75,47%) and the least was a stylus (1,88%), tubers (1,88%), bark (1,88%), and the sap (1,88%). Processing plants as the drug most widely used is by boiling (52,84%) and the least used by way of squeezed (0,81%).